Molecular Frontiers in Modest Labs: Phage Research in Low-Income Settings (World Journal of Experimental Biosciences, 2025)
The establishment of the World Journal of Experimental Biosciences marks a significant milestone for researchers worldwide. For those of us working in low-income countries, it offers a rare platform to voice not only our scientific findings but also the silent struggles behind them. As a former PhD student in India and now a mentor in Ethiopia (Africa), I write this editorial to reflect on the challenges and quiet triumphs of conducting molecular microbiology, especially phage research, in modest laboratories.